2022
DOI: 10.1101/2022.10.14.22281090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The science of child and adolescent mental health in Greece: a nationwide systematic review of the literature

Abstract: Background Evidence-based information is essential to delivering effective mental health care, yet the extent and accessibility of the scientific literature are critical barriers for professionals and policymakers. To map the necessities and make validated resources accessible, we undertook a comprehensive analysis of scientific evidence on child and adolescent mental health in Greece. Methods This systematic review encompasses three research topics related to the mental health of children and adolescents in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…This intends to optimize scientific efforts, amplifying its dissemination and thus increasing possible applications. We recently reviewed publications on prevalence estimates, assessment tools, and intervention trials published in Greece (Koumoula et al 2022) and found that most of the datasets were not freely available, hindering progress and reuse of data to answer relevant questions to child mental health in Greece.…”
Section: Introductionmentioning
confidence: 99%
“…This intends to optimize scientific efforts, amplifying its dissemination and thus increasing possible applications. We recently reviewed publications on prevalence estimates, assessment tools, and intervention trials published in Greece (Koumoula et al 2022) and found that most of the datasets were not freely available, hindering progress and reuse of data to answer relevant questions to child mental health in Greece.…”
Section: Introductionmentioning
confidence: 99%